A Prussian blue positive electrode material and preparation method thereof and sodium ion battery
By controlling the particle size distribution and co-precipitation reaction conditions, a dense Prussian blue positive electrode material was prepared, which solved the problem of low compaction density of Prussian blue materials and improved the capacity and cycle stability of sodium ion batteries.
Patent Information
- Application Number
- CN202211738732.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The rapid nucleation speed of Prussian blue cathode materials leads to a small particle size and low compaction density, which affects its electrochemical performance in sodium ion batteries.
By controlling the particle size distribution in bimodal distribution, the apex peaks of the bimodal are located between 0.7μm-2.2μm and 3μm-9μm, combined with the coprecipitation reaction of high concentration transition metal salt and complexing agent, the droplet ins are adjusted. Flow rate and stirring conditions, a dense Prussian blue cathode material was prepared.
The compaction density and electrochemical performance of Prussian blue cathode materials are improved, and the capacity and cycle stability of sodium ion batteries are enhanced.
Smart Images

Figure CN116002717B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a Prussian blue positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Since its commercialization, lithium-ion batteries have been widely used in 3C and electric vehicles due to their high capacity, high energy density, and long cycle life. However, global lithium resources are limited, and there are disadvantages such as low abundance in the earth's crust and uneven distribution. Sodium is highly abundant in the earth's crust and widely distributed. Sodium and lithium belong to the same main group and have similar physical and chemical properties. Therefore, the significant cost advantage makes sodium-ion batteries have broad application prospects in the fields of energy storage and electric vehicles.
[0003] Prussian blue (white) and its analogs have the advantages of high voltage platform, high gram capacity, excellent cycle performance and low cost due to their open three-dimensional framework structure, and are cathode materials with great application prospects. However, in the current preparation process of Prussian blue, the nucleation speed is too fast, resulting in small particle size and low compaction density. The compaction density of conventional Prussian blue materials is only 0.2g / cm 3 -0.4g / cm 3 , which has an adverse effect on the processing performance and energy density of the positive electrode material. Therefore, it is necessary to find a suitable preparation process to improve the performance of Prussian blue materials so that when they are applied to sodium ion batteries, the electrochemical performance of the battery is improved. Summary of the invention
[0004] The purpose of the present application is to provide a Prussian blue positive electrode material and a preparation method thereof and a sodium ion battery. By making the particle size distribution present a bimodal distribution, the gaps between the granular materials with larger particle sizes are more densely filled with particles with smaller particle sizes, thereby improving the compactness and improving the problem of too low compaction density of the Prussian blue material. When the material is applied to a sodium ion battery, the capacity of the battery is increased.
[0005] To achieve the above objectives, the technical solution of this application is as follows:
[0006] In a first aspect, the present application provides a Prussian blue-based cathode material, wherein the particle size distribution of the Prussian blue-based cathode material is bimodal, and the apex peaks of the bimodal peaks are respectively located between 0.7 μm and 2.2 μm and between 3 μm and 9 μm.
[0007] In combination with the first aspect, as some optional schemes of the present application, the lateral distance between the apexes of the double peaks is L, wherein 0 μm<L<3.6 μm.
[0008] In combination with the first aspect, as some optional solutions of the present application, the Prussian blue positive electrode material satisfies at least one of the following conditions:
[0009] a. The molecular structure of the Prussian blue cathode material is Na 1+x M a [Fe(CN) 6 ] y ·zH 2 O, wherein 0.5≤x≤1, 0≤y≤1, 0<a<3, 0≤z≤4; M is a transition metal element, including at least one of Mn, Fe, Ni, Co, Cu, and Zn;
[0010] b. The particle size D50 of the Prussian blue cathode material is 2 μm-5 μm;
[0011] c. The Span value of the Prussian blue cathode material is 1-1.5, and the Span value = (D90-D10) / D50;
[0012] d. The compaction density of the Prussian blue cathode material is A, where 1 g / cm 3 <A<2g / cm 3 .
[0013] In a second aspect, the present application also provides a method for preparing a Prussian blue positive electrode material, comprising:
[0014] dissolving a transition metal salt and an antioxidant in water to form a first solution;
[0015] dissolving sodium ferrocyanide and a sodium supplement in water to form a second solution;
[0016] dissolving a complexing agent in water to form a third solution;
[0017] The first solution and the third solution are simultaneously dripped into the second solution at different flow rates to perform a coprecipitation reaction, thereby obtaining the Prussian blue positive electrode material.
[0018] In combination with the second aspect, as some optional solutions of the present application, the preparation method satisfies at least one of the following conditions:
[0019] e. The transition metal salt comprises at least one of a transition metal nitrate, a transition metal acetate and a transition metal sulfate;
[0020] f. The antioxidant comprises at least one of vitamin C and citric acid;
[0021] g. The sodium supplement comprises at least one of sodium sulfate, sodium chloride, sodium nitrate, sodium acetate and sodium carbonate;
[0022] h. The complexing agent comprises at least one of sodium citrate, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, and sodium pyrophosphate;
[0023] i. The concentration of the transition metal salt in the first solution is 0.5 mol / L-2 mol / L;
[0024] j. The concentration of the antioxidant in the first solution is 0-1.5 g / L;
[0025] k. The concentration of sodium ferrocyanide in the second solution is 0.1 mol / L-2 mol / L;
[0026] l. The concentration of the sodium supplement in the second solution is 0-2 mol / L;
[0027] m. The concentration of the complexing agent in the third solution is 0.5 mol / L-2 mol / L;
[0028] n. The molar ratio of the transition metal salt to the sodium ferrocyanide is 2-0.5.
[0029] In combination with the second aspect, as some optional schemes of the present application, the preparation method further satisfies at least one of the following conditions:
[0030] o. The pH value of the first solution is 2-3;
[0031] p. The entire process of the coprecipitation reaction is carried out under a protective gas atmosphere, wherein the protective gas comprises at least one of nitrogen and argon;
[0032] q. The temperature required for the coprecipitation reaction is 40°C-75°C;
[0033] r. When the coprecipitation reaction is carried out, the stirring speed in the second solution is 500rpm-700rpm;
[0034] s. The ratio of the dripping flow rate of the first solution to the dripping flow rate of the third solution is 1:(2-4);
[0035] t. The hourly dripping rate of the first solution is 0.7%-1% of the total capacity of the reaction container.
[0036] As some optional schemes of the present application, after the coprecipitation reaction is carried out for a period of time, the method further comprises:
[0037] Stop dripping the first solution and the third solution, and continue stirring the mixed solution formed after the dripping, then drip the first solution and the third solution again, and perform coprecipitation reaction again, then stop dripping, perform aging, filtering, washing, and drying to obtain the Prussian blue positive electrode material.
[0038] In some preferred embodiments, at least one of the following conditions is also met:
[0039] u. The coprecipitation reaction time is 15h-25h;
[0040] v. The stirring time is continued for 5h-15h;
[0041] w. The coprecipitation reaction time is 15h-25h again;
[0042] x. During the entire process of continuing stirring, conducting the coprecipitation reaction again, and conducting the aging, the required protective gas atmosphere, temperature, and stirring speed remain unchanged.
[0043] In combination with the second aspect, as some optional solutions of the present application, after forming the first solution, the second solution and the third solution, the method further includes:
[0044] Dropping the first solution into the second solution to form a first precursor solution, and then dropping the first precursor solution into the third solution to perform the coprecipitation reaction;
[0045] Alternatively, the first solution is dripped into the third solution to form a second precursor solution, and then the second precursor solution is dripped into the second solution to perform the coprecipitation reaction.
[0046] In a third aspect, the present application further provides a sodium ion battery, the raw materials of which include the Prussian blue positive electrode material described in the first aspect above, or the raw materials of which include the Prussian blue positive electrode material prepared by the preparation method described in the second aspect above.
[0047] Beneficial effects of this application:
[0048] The particle size distribution of the Prussian blue positive electrode material in the present application is bimodal, so that when the material is compacted, the gaps between the larger particles are more tightly filled with smaller particles, thereby improving the compactness and improving the problem of too low compaction density of the Prussian blue positive electrode material. When it is applied to sodium ion batteries, the capacity of the battery is increased.
[0049] The preparation method of the Prussian blue positive electrode material of the present application is simple and convenient. By forming a solution of the complexing agent alone and then reacting it with other reaction solutions, and by changing the flow rate of the solution dripping, the particle crystallization rate of the Prussian blue positive electrode material can be flexibly controlled, and then the particle size and particle size distribution of the material can be controlled. The prepared product has few crystal defects, and the problem of too low compaction density of the product is also improved.
[0050] The sodium ion battery of the present application uses the above-mentioned Prussian blue positive electrode material, and has excellent electrochemical performance, high gram capacity and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of the present invention.
[0052] Figure 1 This is a scanning electron microscope image of the Prussian blue positive electrode material prepared in Example 1;
[0053] Figure 2 This is a scanning electron microscope image of the Prussian blue positive electrode material prepared in Comparative Example 1;
[0054] Figure 3 This is a scanning electron microscope image of the Prussian blue positive electrode material prepared in Comparative Example 2;
[0055] Figure 4 This is a particle size distribution diagram of the Prussian blue positive electrode material prepared in Example 1;
[0056] Figure 5 This is a particle size distribution diagram of the Prussian blue positive electrode material prepared in Comparative Example 1;
[0057] Figure 6 This is the particle size distribution diagram of the Prussian blue positive electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0058] As used herein:
[0059] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0060] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0061] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0062] In these examples, parts and percentages are by mass unless otherwise indicated.
[0063] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0064] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0065] In a first aspect, the present application provides a Prussian blue-based cathode material, wherein the particle size distribution of the Prussian blue-based cathode material is bimodal, and the apex peaks of the bimodal peaks are respectively located between 0.7 μm and 2.2 μm and between 3 μm and 9 μm.
[0066] In some optional embodiments of the present application, the lateral distance between the apex of the double peaks is L, 0μm<L<3.6μm. It is understandable that if the particle size corresponding to the apex of one of the double peaks is 1.3μm, the particle size corresponding to the apex of the other peak is between 3μm-4.9μm, and does not include the two endpoint values.
[0067] In some optional embodiments of the present application, the molecular structure of the Prussian blue positive electrode material is Na 1+x M a [Fe(CN) 6 ] y ·zH 2O. Wherein 0.5≤x≤1, 0≤y≤1, 0<a<3, 0≤z≤4; M is a transition metal element, specifically including at least one of Mn, Fe, Ni, Co, Cu and Zn.
[0068] It can be understood that 0.5≤x≤1 indicates that the sodium content in the structure of Prussian blue-based positive electrode materials is relatively high. When applied to sodium ion batteries, it can increase the battery's charge and discharge specific capacity and also improve the stability of the material structure.
[0069] In some optional embodiments of the present application, the particle size D50 of the Prussian blue positive electrode material is 2 μm-5 μm, for example, it can be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any value between 2 μm and 5 μm. More preferably, the particle size D50 of the Prussian blue positive electrode material is 3.076 μm.
[0070] In some optional embodiments of the present application, the Span value of the Prussian blue positive electrode material is 1-1.5, for example, it can be 1, 1.1, 1.2, 1.3, 1.4, 1.5 or any value between 1 and 1.5. More preferably, the Span value of the Prussian blue positive electrode material is 1.27.
[0071] Among them, Span value = (D90-D10) / D50. Generally, the larger the Span value, the wider the particle size distribution of the material particle group, and the smaller the Span value, the narrower the particle size distribution of the material particles and the more uniform the particles.
[0072] By controlling the particle size, Span value, and lateral distance between the double peak vertices within an appropriate range, it is possible to avoid the situation where the particle size of the material particles is too large or the specific surface area is too low, resulting in the sodium ion diffusion path being too long when the material is used in a sodium ion battery, thus affecting the material's cycle performance; or the particle size of the material particles is too small or the specific surface area is too high, resulting in side reactions on the material surface, causing the battery's cycle performance to deteriorate. This can ensure the cycle performance of such materials.
[0073] In some optional embodiments of the present application, the compacted density of the Prussian blue material is A, wherein 1.0 g / cm 3 <A<2g / cm 3 , for example, it can be 1.1 g / cm 3 , 1.2g / cm 3 , 1.4g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 or 1.9g / cm 3 .
[0074] The compaction density of the Prussian blue cathode material prepared in this application is greater than 1.0 g / cm3 , which can improve the battery energy density and optimize its capacity performance.
[0075] In a second aspect, the present application also provides a method for preparing the Prussian blue material described in the first aspect, comprising:
[0076] Dissolving a transition metal salt and an antioxidant in water to form a first solution; dissolving sodium ferrocyanide and a sodium supplement in water to form a second solution; and dissolving a complexing agent in water to form a third solution;
[0077] Then, the first solution and the third solution are simultaneously dripped into the second solution at different flow rates to perform a co-precipitation reaction, thereby obtaining the Prussian blue positive electrode material.
[0078] In combination with the second aspect, in some optional methods of the present application, after forming the first solution, the second solution and the third solution, it also includes: dripping the first solution into the second solution to form a first precursor solution, and then dripping the first precursor solution into the third solution to carry out the co-precipitation reaction; or, dripping the first solution into the third solution to form a second precursor solution, and then dripping the second precursor solution into the second solution to carry out the co-precipitation reaction.
[0079] It should be noted that in addition to forming a separate solution of the complexing agent solution, other reactants such as sodium ferrocyanide and transition metal salts also form different solutions. By changing the order of adding the sodium ferrocyanide solution and the transition metal salt solution, Prussian blue positive electrode materials can also be prepared.
[0080] In some optional embodiments of the present application, the transition metal salt includes at least one of a transition metal nitrate, a transition metal acetate and a transition metal sulfate.
[0081] In some optional embodiments of the present application, the antioxidant includes at least one of vitamin C and citric acid.
[0082] In some optional embodiments of the present application, the sodium supplement includes at least one of sodium sulfate, sodium chloride, sodium nitrate, sodium acetate and sodium carbonate.
[0083] In some optional embodiments of the present application, the complexing agent includes at least one of sodium citrate, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, and sodium pyrophosphate.
[0084] In some optional embodiments of the present application, the concentration of the transition metal salt in the first solution is 0.5 mol / L-2 mol / L, for example, it can be 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L or any value between 0.5 mol / L and 2 mol / L.
[0085] In some optional embodiments of the present application, the concentration of the antioxidant in the first solution is 0-1.5 g / L, for example, 0, 0.2 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 1.2 g / L, 1.5 g / L or any value between 0-1.5 g / L. It is understood that in some cases, the antioxidant may not be added to the first solution.
[0086] In some optional embodiments of the present application, the concentration of sodium ferrocyanide in the second solution is 0.1mol / L-2mol / L, for example, it can be 0.1mol / L, 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L or any value between 0.1mol / L-2mol / L.
[0087] In some optional embodiments of the present application, the concentration of the sodium supplement in the second solution is 0-2 mol / L, for example, it can be 0, 0.2 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L or any value between 0-2 mol / L.
[0088] In some optional embodiments of the present application, the concentration of the complexing agent in the third solution is 0.5mol / L-2mol / L, for example, it can be 0.5mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 2mol / L or any value between 0.5mol / L and 2mol / L.
[0089] In some optional embodiments of the present application, the molar ratio of the transition metal salt to the sodium ferrocyanide is (2-0.5):1, for example, it can be 2:1, 1.5:1, 1:1, 0.5:1 or any value between (2-0.5):1.
[0090] In some optional embodiments of the present application, the pH value of the first solution is 2-3, for example, it can be 2, 2.2, 2.5, 2.7, 3 or any value between 2-3.
[0091] It should be noted that if it is necessary to ensure that the pH of the first solution is within the range of 2-3, some acidic substances, such as citric acid, may be added to the water for adjustment.
[0092] In the common chelating agent-assisted coprecipitation method, for high-concentration transition metal salt solutions, if a high chelating agent dosage is used, the pH of the solution will be too high (about 5), causing the transition metal and the hydroxide ion to precipitate. Therefore, it is usually not possible to use a high chelating agent dosage to control the crystallization rate of particles in high-concentration metal liquids; and a low chelating agent dosage cannot control the particle nucleation rate, resulting in many crystal defects, which greatly affects the material properties. If the concentration of the transition metal salt solution is reduced to a low concentration range of 0.002mol / L-0.01mol / L, the yield will be low.
[0093] The preparation process of the present application can not only use a high concentration (0.5 mol / L-2 mol / L) transition metal salt solution to increase production capacity, but also introduce a complexing agent solution into the reactants alone for a coprecipitation reaction. By changing the dripping method of the sodium ferrocyanide solution, the transition metal salt solution and the dispersant solution, the crystallization rate of the Prussian blue material particles can be flexibly controlled, thereby controlling the particle size and particle size distribution of the material. The prepared product has fewer crystal defects and also improves the problem of too low compaction density of the product. The process is a simple method for preparing Prussian blue materials with high capacity and good circulation.
[0094] In some optional embodiments of the present application, the entire process of the coprecipitation reaction is carried out under an atmosphere of protective gas, and the protective gas includes at least one of nitrogen and argon.
[0095] In some optional embodiments of the present application, the temperature required for the coprecipitation reaction is 40°C-75°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or any value between 40°C and 75°C.
[0096] In some optional embodiments of the present application, when performing a coprecipitation reaction, the stirring speed in the second solution is 500rpm-700rpm, for example, it can be 500rpm, 550rpm, 600rpm, 650rpm, 700rpm or any value between 500rpm-700rpm.
[0097] In some optional embodiments of the present application, the ratio of the dripping flow rate of the first solution to the dripping flow rate of the third solution is 1:(2-4), for example, it can be 1:2, 1:3, 1:4 or any value in between 1:(2-4).
[0098] In some optional embodiments of the present application, the hourly dripping rate of the first solution is 0.7%-1% of the total capacity of the reaction container, for example, it can be 0.7%, 0.8%, 0.9%, 1% or any value between 0.7%-1%. It is understandable that if the total capacity of the reaction container is 500mL, the dripping rate volume of the first solution is 3.5mL / h-5mL / h.
[0099] In some optional embodiments of the present application, after the coprecipitation reaction is carried out for a period of time, it also includes: stopping the dripping of the first solution and the third solution, and continuing to stir the mixed solution formed after the dripping, and then dripping the first solution and the third solution again, and carrying out the coprecipitation reaction again, and then stopping the dripping, aging, filtering, washing, and drying to obtain the Prussian blue material.
[0100] In some preferred embodiments, the coprecipitation reaction time is 15h-25h, more preferably 20h; the stirring time is 5h-15h, more preferably 20h; the coprecipitation reaction time is again 15h-25h, more preferably 20h.
[0101] In addition, during the whole process of continuing stirring, coprecipitation reaction again and aging, the protective gas atmosphere protection, the temperature and the stirring speed need to be maintained at the same level, and these required protective gas atmosphere, temperature and stirring speed remain the same as the parameters required for the previous coprecipitation reaction. This can improve the stability of the coprecipitation reaction and ensure that the particle size distribution of the particles is not too dispersed.
[0102] The present application also provides a sodium ion battery, the raw materials of which include the Prussian blue positive electrode material described in the first aspect above.
[0103] The embodiments of the present invention will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0104] Example 1
[0105] This embodiment provides a Prussian blue positive electrode material, and the preparation method thereof includes:
[0106] (1) Prepare a first solution: including 1.0 mol / L manganese sulfate monohydrate, an appropriate amount of citric acid to maintain the pH at 2-2.2, and 1 g / L vitamin C; prepare a second solution: including 0.2 mol / L sodium ferrocyanide decahydrate and 1.0 mol / L anhydrous sodium sulfate; prepare a third solution: including 1.0 mol / L sodium citrate.
[0107] (2) The first solution and the third solution are slowly added to the second solution at different flow rates, with the flow rate ratio being 1:3, and the flow rate of the first solution being 0.75% / h of the total capacity of the reaction container, to carry out a coprecipitation reaction. The entire reaction process is protected by nitrogen to ensure a low oxygen state; the temperature of the reaction solution is kept constant at 60°C, and the stirring speed when added dropwise to the second solution is 600rpm. After 20 hours of coprecipitation reaction, the addition of the first solution and the third solution is stopped, and stirring is maintained for 10 hours, and the first solution and the third solution are continued to be introduced, and the addition is stopped after the reaction continues for 20 hours.
[0108] (3) Then, the aging was continued for 10 hours, during which the temperature, stirring speed and protective atmosphere were kept unchanged. The white slurry obtained by aging was then filtered and washed with pure water to remove the impurity ions on the surface of the solid filtrate, and then vacuum dried to obtain the Prussian blue positive electrode material, whose chemical formula composition is Na 1.86 MnFe(CN) 6 ·2H 2 O.
[0109] Comparative Example 1
[0110] This comparative example provides a Prussian blue positive electrode material, and its specific preparation method includes:
[0111] (1) Prepare a first solution: including 2.0 mol / L manganese sulfate monohydrate, an appropriate amount of citric acid to maintain the pH at 2-2.2, and 1 g / L vitamin C; prepare a second solution: including 0.5 mol / L sodium ferrocyanide decahydrate, 1.0 mol / L anhydrous sodium sulfate and 0.4 g / L dispersant polyvinyl pyrrolidone; prepare a third solution: including 0.5 mol / L sodium citrate.
[0112] (2) The first solution and the third solution were slowly added to the second solution at different flow rates, with the flow rate ratio being 1:1, and the flow rate of the first solution being 1% / h of the total capacity of the reaction container, to carry out a coprecipitation reaction. The entire reaction process was protected by nitrogen to ensure a low oxygen state; the temperature of the reaction solution was kept constant at 60°C, and the stirring speed of the solution added dropwise to the second solution was 600 rpm. The addition of the first solution and the third solution was stopped after 30 hours of the coprecipitation reaction.
[0113] (3) Then, the aging was continued for 10 hours, during which the temperature, stirring speed and protective atmosphere were kept unchanged. The white slurry obtained by aging was then filtered and washed with pure water to remove the impurity ions on the surface of the solid filtrate, and then vacuum dried to obtain the Prussian blue positive electrode material, whose chemical formula is Na 1.79 MnFe(CN) 6 2.2H 2 O.
[0114] Comparative Example 2
[0115] This comparative example provides a Prussian blue positive electrode material, and its specific preparation method includes:
[0116] (1) Prepare a first solution: including 1.0 mol / L manganese sulfate monohydrate, an appropriate amount of citric acid to maintain the pH at 2-2.2, and 1 g / L vitamin C; prepare a second solution: including 1.0 mol / L sodium ferrocyanide decahydrate and 1.0 mol / L anhydrous sodium sulfate; prepare a third solution: including 1.0 mol / L sodium citrate.
[0117] (2) The first solution and the third solution were slowly added to the second solution at different flow rates, with the flow rate ratio being 1:3, and the flow rate of the first solution being 0.75% / h of the total capacity of the reaction container, to perform a coprecipitation reaction. The entire reaction process was protected by nitrogen to ensure a low oxygen state; the temperature of the reaction solution was kept constant at 60°C, and the stirring speed of the solution added dropwise to the second solution was 600 rpm. The addition of the first solution and the third solution was stopped after the coprecipitation reaction lasted for 20 hours.
[0118] (3) Then, the aging was continued for 10 hours, during which the temperature, stirring speed and protective atmosphere were kept unchanged. The white slurry obtained by aging was filtered and washed with pure water to remove the impurity ions on the surface, and then vacuum dried to obtain the Prussian blue positive electrode with the chemical formula composition of Na 1.79 MnFe(CN) 6 2.4H 2 O.
[0119] Table 1 lists the particle size, particle size distribution and compacted density test results of the Prussian blue particles of Example 1 and Comparative Examples 1-2 after being tested by a Malvern laser particle size analyzer.
[0120] Table 1
[0121]
[0122] The samples prepared in Example 1 and Comparative Examples 1-2 were used as positive electrode materials, respectively. The positive electrode material, binder polyvinylidene fluoride (PVDF), and conductive agent (SuperP) were mixed uniformly in a mass ratio of 8:1:1, and evenly coated on aluminum foil into a thin layer. After drying, they were cut into discs as positive electrode materials, metal sodium sheets were used as negative electrodes, Whatman glass fibers were used as separators, and 1.0 molL-1 NaClO4 / EC (ethylene carbonate) + DMC (dimethyl carbonate) + FEC (fluoroacetate) (the volume ratio of EC to DMC was 1:1, and FEC accounted for 5% of the total volume) was used as electrolyte. CR2032 button batteries were assembled in an argon glove box. The button batteries were subjected to constant current charge and discharge tests, with a charge and discharge voltage range of 2 to 4 V, and were continuously cycled for 50 weeks at a current density of 150 mA / g.
[0123] Table 2 shows the electrochemical performance results of the battery tested after the Prussian blue positive electrode materials prepared in Example 1 and Comparative Examples 1-2 were prepared into batteries.
[0124] Table 2
[0125]
[0126]
[0127] Figure 1 , Figure 2 , Figure 3 The scanning electron microscope images of the Prussian blue positive electrode materials prepared in Example 1 and Comparative Examples 1-2 are shown respectively. Figure 4 , Figure 5 , Figure 6 The particle size distribution diagrams of the Prussian blue positive electrode materials prepared in Example 1 and Comparative Examples 1-2 are shown respectively. Figure 4-Figure 6 It can be seen that the particle size distribution of Example 1 is a bimodal distribution, and the apex peaks of the two peaks are located between 0.7μm-2.2μm and between 3μm-9μm, respectively, with specific values of 1.5μm and 5μm; the lateral distance between the apexes S1 and S2 of the two peaks is 0μm<L<3.6μm, and the Span value is 1.274, indicating that although its particle size is a bimodal distribution, the overall difference in particle size will not be too large; while the particle size distributions of the materials prepared in Comparative Examples 1 and 2 are both unimodal: the D50 of Comparative Example 1 reaches 18.810μm, and the D50 of Comparative Example 2 is only 1.06μm.
[0128] From the compaction density test results in Table 1, it can be seen that the compaction density of Example 1 is significantly higher than that of Comparative Examples 1-2. This is because the gaps between the large particles with larger particle sizes in Example 1 can be more tightly filled with particles with smaller particle sizes, and the packing density per unit volume is improved, thereby improving the problem of too low compaction density of Prussian blue positive electrode materials. When it is applied to sodium ion batteries, the capacity of the battery is improved. The sodium content of Example 1 in Table 1 reaches 1.89, and the crystal water content is low, indicating that there are few crystal defects, which is conducive to the insertion and extraction of sodium ions, further improving the capacity and cycle performance.
[0129] Combining the data results of Example 1 and Comparative Examples 1 and 2 in Table 1 and Table 2, it can be seen that when the particle size of the material particles in Comparative Example 1 is too large and the specific surface area is too small, when it is applied to a sodium ion battery, the capacity and cycle retention rate of the battery are low. This is because during the charge and discharge process, the resistance to the diffusion of sodium ions and the transmission of electrons increases, and the electrolyte cannot be fully infiltrated, resulting in a long diffusion path for sodium ions. Due to the small particle size and large specific surface area of Comparative Example 2, side reactions are easily produced on the surface of the material, resulting in poor cycle performance. The material in Example 1 has a suitable specific surface area, and the steps formed by the mutual adhesion and stacking of the surfaces of each particle provide a large number of active sites and conductive agent attachment points for the redox reaction, while shortening the ion transmission distance and improving the capacity and cycle stability.
[0130] In summary, the particle size distribution of the Prussian blue cathode material prepared in the present application is bimodal, so that when the material is compacted, the gaps between the larger particles are more tightly filled with smaller particles, thereby improving the compactness and improving the problem of too low compaction density of the Prussian blue cathode material, thereby increasing the capacity of the battery; the appropriate particle size and particle size distribution can shorten the ion transmission distance, improve the capacity and cycle stability; the high sodium content and low crystalline water content make the material have fewer crystal defects, which is conducive to the embedding and extraction of sodium ions, further improving the capacity and cycle performance.
[0131] The preparation method of the Prussian blue positive electrode material provided in the present application can not only use a high-concentration transition metal salt solution to increase production capacity, but also pass the complexing agent solution alone into the reactants for co-precipitation reaction. By changing the dripping method of the sodium ferrocyanide solution, the transition metal salt solution and the dispersant solution, the crystallization rate of the Prussian blue material particles can be flexibly controlled to control the particle size and particle size distribution of the material, so that the prepared material has fewer crystal defects and also improves the problem of too low compaction density of the product.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
[0133] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and to form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A Prussian blue positive electrode material, characterized in that: The particle size distribution of the Prussian blue positive electrode material is bimodal, and the apex peaks of the bimodal are respectively located between 0.7 μm and 2.2 μm and between 3 μm and 9 μm; The lateral distance between the apexes of the double peaks is L, where 0 μm < L < 3.6 μm; The particle size D50 of the Prussian blue positive electrode material is 2 μm-5 μm; The Span value of the Prussian blue positive electrode material is 1-1.5, and the Span value = (D90-D10) / D50; The molecular structure of the Prussian blue positive electrode material is Na 1+x M a [Fe(CN)6] y ·zH2O, wherein 0.5≤x≤1, 0<y≤1, 0<a<3, 0≤z≤4; M is a transition metal element, including at least one of Mn, Fe, Ni, Co, Cu, and Zn.
2. The Prussian blue positive electrode material according to claim 1, characterized in that The compaction density of the Prussian blue positive electrode material is A, where 1g / cm 3 <A<2g / cm 3 .
3. A method for preparing a Prussian blue positive electrode material, characterized in that: include: dissolving a transition metal salt and an antioxidant in water to form a first solution; dissolving sodium ferrocyanide and a sodium supplement in water to form a second solution; dissolving a complexing agent in water to form a third solution; The first solution and the third solution are simultaneously dripped into the second solution at different flow rates to perform a coprecipitation reaction; After the coprecipitation reaction is carried out for a period of time, the method comprises: Stop dripping the first solution and the third solution, continue stirring the mixed solution formed after the dripping, then drip the first solution and the third solution again, and perform a coprecipitation reaction again, then stop dripping, perform aging, filtering, washing, and drying to obtain the Prussian blue positive electrode material; The concentration of the antioxidant in the first solution is 0-1.5 g / L; The concentration of the sodium supplement in the second solution is 0-2 mol / L; The ratio of the dripping flow rate of the first solution to the dripping flow rate of the third solution is 1:(2-4).
4. The preparation method according to claim 3, characterized in that: The preparation method satisfies at least one of the following conditions: c. The transition metal salt comprises at least one of a transition metal nitrate, a transition metal acetate and a transition metal sulfate; d. The antioxidant comprises at least one of vitamin C and citric acid; e. The sodium supplement comprises at least one of sodium sulfate, sodium chloride, sodium nitrate, sodium acetate and sodium carbonate; f. The complexing agent comprises at least one of sodium citrate, ethylenediamine, ethylenediaminetetraacetic acid, trisodium nitrilotriacetate, and sodium pyrophosphate; g. The concentration of the transition metal salt in the first solution is 0.5 mol / L-2 mol / L; h. The concentration of sodium ferrocyanide in the second solution is 0.1 mol / L-2 mol / L; i. The concentration of the complexing agent in the third solution is 0.5 mol / L-2 mol / L; j. The molar ratio of the transition metal salt to the sodium ferrocyanide is 2-0.
5.
5. The preparation method according to claim 3, characterized in that: The preparation method satisfies at least one of the following conditions: k. The pH value of the first solution is 2-3; l. The entire process of the coprecipitation reaction is carried out under a protective gas atmosphere, wherein the protective gas comprises at least one of nitrogen and argon; m. The temperature required for the coprecipitation reaction is 40°C-75°C; n. When the coprecipitation reaction is carried out, the stirring speed in the second solution is 500rpm -700rpm; o. The hourly drip rate of the first solution is 0.7%-1% of the total capacity of the reaction vessel.
6. The preparation method according to claim 3, characterized in that: At least one of the following conditions is met: q. The coprecipitation reaction time is 15h-25h; r. The stirring time is continued for 5h-15h; s. The coprecipitation reaction time is 15h-25h again; t. During the whole process of continuing stirring, carrying out the coprecipitation reaction again and carrying out the aging, the required protective gas atmosphere, temperature and stirring speed remain unchanged.
7. A sodium ion battery, characterized in that: The raw material includes the Prussian blue positive electrode material described in any one of claims 1-2, or the raw material includes the Prussian blue positive electrode material prepared by the preparation method described in any one of claims 3-6.
